Management of post-stroke pain - V, Posai (Biomedical Sciences and Clinical Medicine, 2021)
Pain is defined as an unpleasant sensory and emotional experience associated with actuality or potential tissue damage. It is a complicated issue and results from an individual’s experience, making different pain conditions among individuals. Stroke patients are revealed that the pain is from damaged brain tissues caused by an ischemic stroke and brain hemorrhages, physiological change, and disability after the stroke. It is a frequently found trouble and persists in hurting the patients physically, emotionally, psychosocially, and spiritually. Thus, pain management and effective care are substantial. Pain management consists of accurate pain examination and evaluation by standardized instruments for accurate information and practical pain relief methods, serving the needs of patients and their families. This article concludes the frequent pain symptoms found in stroke patients, pain effect, pain evaluation, and holistic pain management for effective stroke patient care.